The Perception of Wroclaw as a Liveable City - Daszkiewicz, Magdalena; Mazurek, Edyta (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
Contemporary cities face the increasing global competition and the necessity to take actions for retaining and attracting residents, tourists, business and investments and highly qualified human capital. Retaining and attracting talented young people may be at the heart of growing a high prosperity of cities. As we know young people are the most likely demographic group to move. The primary challenge for cities is to create places that young talents not only visit, but also treat as attractive places to study, work and live. Therefore, it is important to conduct studies to identify factors affecting city liveability perception and people's decisions regarding the choice of a city as a place to live, study and work. The main aim of the paper is to determine the perception of Wroclaw’s attractiveness as a city to live and identify the impact of selected factors affecting city liveability perception. The logit model is used for the assessment of the effects of explanatory factors on the chance that Wroclaw is perceived as a good place to live. The analysis is made basing on real data from the survey on the attractiveness of Wroclaw through the eyes of international students. We focused on evaluating the overall perception of the liveability of the city, in relation to perception of Wroclaw's liveability for different groups of residents. We also tested if perception of Wroclaw as a liveable city depends significantly on the national wealth of home country of international students. We discuss the findings and provide some managerial implications regarding city development and implications for future research
20-th AMSE. Applications of Mathematics and Statistics in Economics. International Scientific Conference: Szklarska Poręba, 30 August- 3 September 2017. Conference Proceedings Full Text Papers, s. 75-88
Keywords: city attractiveness; city liveability; perceived liveability; logit model; categorical data